Pensando o e a artista-docente em teatro: expressões e sensibilidades na trajetória de egressos e egressas do curso de licenciatura em Artes Cênicas (UFGD) - Oliveira Júnior, Antonio Martins (2023)
This work presents an analysis of the role and conceptualization of the artist-teacher in theater. The research focuses on the trajectory of professionals who have graduated from the undergraduate program in Performing Arts Education at UFGD, exploring the construction of a teaching practice that integrates art and pedagogy, considering artistic intersections, sensibilities, expressions, and experiences throughout this journey. Through the contributions and reflections of the collaborators involved in the research, it was possible to understand that the formation and work of the artist-teacher are not solely determined by the disciplines and curriculum offered by the program, but also by the individual interests of each professional in seeking specific experiences that were present or absent during their academic training, experiences that shaped their professional trajectories, whether working in primary schools or independent cultural centers.